Bargaining over Australian public service cuts: Do forcing strategies work?. (March 2016) - Williamson, Sue; O'Donnell, Michael; Roles, Cameron
Although a Labor government fiscal stimulus had helped Australia weather the 2008 global financial crisis, budget deficits increased, and the public service was targeted for economies. The Liberal/National (Coalition) opposition won office in 2013, promising public sector cuts. In this context, the Walton et al. concept of a forcing strategy helps analyse the 2014–2016 bargaining round in the Australian Public Service. A forcing strategy involves three negotiating processes: distributive bargaining to achieve concessions in pay and working conditions, the structuring of attitudes to heighten animosity between the negotiating parties, and the management of internal differences to minimise intragroup conflicts. The Liberal/National (Coalition) government adopted elements of these approaches, requiring Australian Public Service agencies to reduce a range of employment conditions to justify pay increases. Interactions between Australian Public Service management and the principal Australian Public Service trade union, the Community and Public Sector Union became increasingly hostile over the course of the bargaining round. In addition, internal differences emerged between the Australian Public Service Commission, which oversaw the bargaining process, and individual Australian Public Service agencies. We consider the efficacy of this forcing strategy in light of the potential for the Community and Public Sector Union to mobilise its membership to resist such an approach to pay negotiations.